2019
DOI: 10.1016/j.heliyon.2019.e01517
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community shifts in the oxic-settling-anoxic process in response to changes to sludge interchange ratio

Abstract: This particular study set out to demonstrate alterations on the microbial community of the oxic-settling-anaerobic/anoxic (OSA) process treating real domestic wastewater by changing interchange ratios (IRs). The sludge yield of systems operated at different IRs (1/13, 1/17 and 1/20) to assess sludge reduction was used to analyze microbial community composition variations. The highest IR (1/13) resulted in the highest sludge reduction (52.1%), while the OSA systems with IR of 1/17 and 1/20 reduced sludge produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Similarly, using the DGGE fingerprint technique it was shown that Proteobacteria and Bacteroidetes species were the most abundant in the OSA process [66]. The finding is consistent with findings of the later study by [64] using Next Generation Sequencing (NGS) of bacterial 16S rRNA gene amplicons, which showed that Proteobacteria, Actinobacteria, Bacteroidetes, and Chloroflexi were also predominant phyla in OSA systems in which their proportions in the microbial community distinguished due to the different IRs applied during the operation period. But surprisingly, Thiotrichaceae (phylum: Proteobacteria) species were not detected in the seed sludge sample, the majority of the total sequences were represented by Thiotrichaceae at the family level in all OSA systems and the genus level, Thiothrix was the predominant one.…”
Section: Variation Of Microbial Culture Population In Osa Processsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, using the DGGE fingerprint technique it was shown that Proteobacteria and Bacteroidetes species were the most abundant in the OSA process [66]. The finding is consistent with findings of the later study by [64] using Next Generation Sequencing (NGS) of bacterial 16S rRNA gene amplicons, which showed that Proteobacteria, Actinobacteria, Bacteroidetes, and Chloroflexi were also predominant phyla in OSA systems in which their proportions in the microbial community distinguished due to the different IRs applied during the operation period. But surprisingly, Thiotrichaceae (phylum: Proteobacteria) species were not detected in the seed sludge sample, the majority of the total sequences were represented by Thiotrichaceae at the family level in all OSA systems and the genus level, Thiothrix was the predominant one.…”
Section: Variation Of Microbial Culture Population In Osa Processsupporting
confidence: 85%
“…Various specific molecular methodologies have been applied to document and compare the microbial culture structure and population dynamics in control and OSA process systems [21], [26], [33] , [36], [64], [65]. Microbial communities can be strongly affected by diverse factors [66].…”
Section: Variation Of Microbial Culture Population In Osa Processmentioning
confidence: 99%
“…Manure, food waste, and municipal sewage sludge (SS) are examples of water-rich biomass resources that HTL can eliminate without resorting to incineration, which is the most popular method of disposal in the US, Japan, and Europe. 101 According to estimates, SS is generated at a rate of 75–100 MLT of dry solids (DS) annually 102 and is expected to increase to 127.5 MLT DS by 2030 103 Additionally, 17% of the food produced worldwide is wasted annually, 104 amounting to roughly 1.3 billion tonnes (BLT), 105 and the annual production of manure is estimated to be between 15–20 MLT. 106 All of these biomasses produce constantly and have the potential to be used as feedstocks for the manufacturing of SAFs.…”
Section: Future Prospective: Technology and Feedstocks For Safs Produ...mentioning
confidence: 99%
“…Presently, the MSS as DS produced annually for more than 100,000 WWTPs operating worldwide amounts to a minimum of 45 [130], although a more realistic estimate is 75-100 million tons. According to Shanmugam et al [131], global sewage sludge production is predicted to reach 127.5 million tons as DS by 2030.…”
Section: Mss Disposal and Nutrient And Chemical Recoverymentioning
confidence: 99%